Using collective of agents for exploration of graph - Andrey Viktorovich Stepkin (Компьютерные исследования и моделирование, 2013)
Problem of exploration finite undirected graphs by a collective of agents is considered in this work. Two agents-researchers simultaneously move on graph, they read and change marks of graph elements, transfer the information to the agent-experimenter (it builds explored graph representation). It was constructed an algorithm linear (from amount of the graphs nodes) time complexity, quadratic space complexity and communication complexity, that is equal to O(n2·log(n)). Two agents (which move on graph) need two different colors (in total three colors) for graph exploration. An algorithm is based on depth-first traversal method.